Synthesis, Characterization, Theoretical Crystal Structure and Antibacterial Activities of Some Transition Metal Complexes of The Thiosemicarbazone (Z)-2-(Pyrrolidin-2-Ylidene)Hydrazinecarbothioamide - Al-Amiery, Ahmed A H; Al-Majedy, Yasmien K; Razzaq, Hazim Abdul; Abood, Hussain (Al-Nahrain Journal of Science, 2018)
Problem statement: In Iraq like most third world countries, attempts to discovered a new antibiotic drugs derived from thiosemcarbazied and its metal complexes moreover develop the branch of applied in organic chemistry. Approach: New (Z)-2-(pyrrolidin-2-ylidene) hydrazinecarbo thioamide (L) was synthesized in a good yield by the reaction of pyrrolidone with thiosemicarbazide. Co(II), Ni(II), and Cu(II) complexes of (L) were prepared, and characterized by FT-IR, UV/visible spectra, 1HNR, and CHN analysis moreover charge, bond length, bond angle, twist angle, heat of formation and steric energy were calculate by using of ChemOffice program. The free ligand and its metal complexes were tested in vitro against a number of microorganisms (Staphylococcus aurous, E.coli, Proteus vulgaris, Pseudomonas, and Klebsiella) in order to assess their antimicrobial properties. Results: The study indicates that these complexes have octahedral geometry, in addition it have high activity against tested bacteria. Conclusion/Recommendations: Based on the reported results, it may be concluded that ligand act as bidentate uninegative ligand, coordinating through one of the nitrogen atom and the sulfur atoms.